Hybrid seed incompatibility in Capsella is connected to chromatin condensation defects in the endosperm - Dziasek, Katarzyna; Simon, Lauriane; Lafon-Placette, Clément; Laenen, Benjamin; Wärdig, Cecilia; Santos-González, Juan; Slotte, Tanja; Köhler, Claudia (PLoS genetics, 2021)
Hybridization of closely related plant species is frequently connected to endosperm arrest and seed failure, for reasons that remain to be identified. In this study, we investigated the molecular events accompanying seed failure in hybrids of the closely related species pair Capsella rubella and C. grandiflora. Mapping of QTL for the underlying cause of hybrid incompatibility in Capsella identified three QTL that were close to pericentromeric regions. We investigated whether there are specific changes in heterochromatin associated with interspecific hybridizations and found a strong reduction of chromatin condensation in the endosperm, connected with a strong loss of CHG and CHH methylation and random loss of a single chromosome. Consistent with reduced DNA methylation in the hybrid endosperm, we found a disproportionate deregulation of genes located close to pericentromeric regions, suggesting that reduced DNA methylation allows access of transcription factors to targets located in heterochromatic regions. Since the identified QTL were also associated with pericentromeric regions, we propose that relaxation of heterochromatin in response to interspecies hybridization exposes and activates loci leading to hybrid seed failure.
Keywords: Heterochromatin; Genes, Plant; DNA Methylation; chromozomální aberace; heterochromatin; metylace DNA; chromatin; Seeds; centromera; lokus kvantitativního znaku; druhová specificita; regulace genové exprese u rostlin; endosperm; Centromere; Chromosome Aberrations; rostlinné geny; Species Specificity; semena rostlinná; Quantitative Trait Loci; Capsella; Chromatin; Gene Expression Regulation, Plant; Hybridization, Genetic; hybridizace genetická; Endosperm